Analysis of risk factors and changing trends the infection rate of intestinal schistosomiasis caused by S. japonicum from 2005 to 2014 in Lushan city. Issue 6 (December 2018) - Xiao, Guoliang; Li, Xinghuo; Jiang, Hongyin; Peng, Zhanghua; Liu, Wei; Lu, Quqin
Abstract: Intestinal schistosomiasis caused by S. japonicum has long been a threat to the health of residents within endemic areas, especially along the mid-tier of the Yangtze River basin as well as the Dongting and Poyang lakes. Therefore, we collected monitoring data from 2005 to 2014 in Lushan City, Jiujiang City, Jiangxi Province, which is located downstream of Poyang Lake. We conducted a logistic regression analysis in 2005 and in 2008 and then conducted a time series analysis from 2005 to 2014 in Lushan city. The results of the logistic regression analysis showed that after integrated measures were implemented in Lushan city in 2004, the infection rate of intestinal schistosomiasis decreased sharply in different populations, but fishermen had a greater risk of contracting intestinal schistosomiasis in both 2005 and 2008. From the time series analysis, we found that the infection rate decreased sharply from 2005 to 2009 and then increased slowly from 2009 to 2011 before finally becoming relatively stable and the predicated infection rates in HES, SM2, and SM3 are −1.14%, 0.35%, 0.29%, respectively, compared with 0.41% of schistosomiasis infection in 2014, showing a downward trend. Our study indicated that the integrated measures initiated in 2004 in Lushan city had a positive effect on controlling intestinal schistosomiasis, but we should still emphasize special treatment of particular populations, such as fishermen, and should consider environmental changes, such as changes in the water level of Poyang Lake, in the future. Graphical abstract: Highlights: Fishermen had a higher risk of contracting Intestinal schistosomiasis compared with other occupations in 2005 and 2008. Although the infection rate of Intestinal schistosomiasis decreased from 2005 to 2014, it fluctuated in some years. Integrated measures are still needed to eliminate Schistosomiasis japonica in the furture.